The Mediating Effect of Tax Fairness on the Relationship Between Knowledge, Complexity and Voluntary Tax Compliance - Che Azmi, Anna Azriati; Zainuddin, Suria; Mustapha, Mohd Zulkhairi; Nawi, Yusni (Asian Journal of Accounting Perspectives, 2016)
This study aims to examine the mediating role of tax fairness on the relationship between tax knowledge, tax complexity, and voluntary tax compliance. Based on 200 samples of taxpayers, it is found that tax knowledge increases tax fairness perceptions, which, consequently, increases tax compliance behaviour. Similarly, tax fairness perceptions do not reduce the tax compliance directly, but indirectly through the role of tax fairness perceptions. This implies that tax authorities should not only focus on introducing or developing tax rules that are fair to the taxpayers but be able to communicate the rationale of a tax rule in the context of how it permeates fairness into the tax system for certain classes of taxpayers. Our study found that, in situations where tax simplification is not possible, this form of information dissemination could lead to better compliance among taxpayers. Keywords: Tax Compliance, Knowledge, Fairness, Complexity JEL Classification: H260